2004
DOI: 10.1191/0269215504cr729oa
|View full text |Cite
|
Sign up to set email alerts
|

Development and preliminary assessment of the measurement properties of the Seating Identification Tool (SIT)1

Abstract: The SIT is a quick, easy to use, reliable and valid screening tool that can be used to facilitate clinical referral for formal intervention. Other potential uses include population-based surveys to estimate the need for including seating intervention in strategic planning for the institutionalized elderly.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 20 publications
2
19
1
Order By: Relevance
“…Raters measured need for wheelchair seating intervention (e.g., problems such as sliding, leaning, pressure ulcers and difficulty propelling), using the Seating Identification Tool (SIT). 16 A score of two or higher indicates the need for seating intervention. Based on our preliminary qualitative study we created a mobility-related variable entitled "wheelchair issues" by summing together five dichotomous variables (yes = 1) that were not included in the SIT: 1) inability to release their seat belt, 2) use of a lap tray, 3) sitting in a wheelchair not designed for self-propulsion, 4) inability to release both brakes, and 5) sitting on a transfer sling.…”
Section: Predictor Variablesmentioning
confidence: 99%
“…Raters measured need for wheelchair seating intervention (e.g., problems such as sliding, leaning, pressure ulcers and difficulty propelling), using the Seating Identification Tool (SIT). 16 A score of two or higher indicates the need for seating intervention. Based on our preliminary qualitative study we created a mobility-related variable entitled "wheelchair issues" by summing together five dichotomous variables (yes = 1) that were not included in the SIT: 1) inability to release their seat belt, 2) use of a lap tray, 3) sitting in a wheelchair not designed for self-propulsion, 4) inability to release both brakes, and 5) sitting on a transfer sling.…”
Section: Predictor Variablesmentioning
confidence: 99%
“…The Seating Identification Tool (SIT) was developed to screen for individuals at risk for functional restriction or health complications due to an inadequately fitted wheelchair prescription [12] . As part of a tool development study, Miller et al [12] reported a prevalence rate of 67% among 43 residents of a single Ontario LTC facility.…”
Section: Prevalence and Predictors Of Need For Wheelchair Assessment mentioning
confidence: 99%
“…Role of aforementioned research, particularly in long-term rehabilitation and care, may be hard to overestimate, influencing both independence, mobility, quality of life, and even, as a consequences, mortality and cost of the therapy in disable people and elderly people. Newest tools, including Seating Identifi cation Tool (SIT), Resident Ergonomic Assessment Profi le for Seating, and Wheelchair Seating Discomfort Assessment Tool, help to assess selected possible risks in a quick, easy to use, reliable and valid way (Gavin-Dreschnack et al, 2005;Miller et al, 2004;Crane et al, 2005). But no doubt outcomes of clinical trials should be involved into strategic planning for both the home therapy and care, and institutionalized therapy and care.…”
Section: Discussionmentioning
confidence: 99%